International Journal of Historical Archaeology - Orser, Charles; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
International Journal of Historical Archaeology is the first authoritative resource for scholarly research on this rapidly growing field. Articles - contributed by an international body of experts - contain current theoretical, methodological, and site-specific research. Exploring a wide-range of topics, articles focus on the post-1492 period and includes studies reaching into the Late Medieval period. In addition, the journal makes global connections between sites, regions, and continents. International Journal of Historical Archaeology will fulfill the needs of archaeologists, students, historians, and historical preservationists as well as practionioners of other closely related disciplines. For more detailed information about this new journal, including complete submission instructions, please visit the http://www.ilstu.edu/~ceorser/ijha.html International Journal of Historical Archaeology Web Site. Rated 'A' in the European Reference Index for the Humanities (ERIH) International Journal of Historical Archaeology is rated 'A' in the ERHI, a new reference index that aims to help evenly access the scientific quality of Humanities research output. For more information visit http://www.esf.org/research-areas/humanities/activities/research-infrastructures.html Rated 'A' in the Australian Research Council Humanities and Creative Arts Journal List. For more information, visit: http://www.arc.gov.au/era/journal_list.htm .
Keywords: Archaeology; Archaeology